Antenatal Health Care Service Utilization in Slum Areas of Pokhara Sub-Metropolitan City, Nepal - Sharma, D; Pokharel, H P; Budhathoki, S S; Yadav, B K; Pokharel, P K (Journal of Nepal Health Research Council, 2016)
Background: Half a million women die every year due to pregnancy and childbirth in the world. Among these death, 99% occur in the low and middle income countries. Antenatal care (ANC) provides an opportunity to deliver different services which are important in improving maternal survival. Methods: A descriptive cross sectional study was conducted from September 2012 - February 2013 among 400 married women of reproductive age group. A pre-tested structured questionnaire were used and data were analyzed using Statistical Package for Social Science(SPSS) for windows version 18.0. Frequency, crude and adjusted odds ratios and confidence intervals were performed. Results: Nearly 27% had four or more antenatal health care utilization(ANC) visits on appropriate time according to schedule of World Health Organization(WHO). In logistic regression, ANC users were found to be more/less likely to be in age group 20 – 35 years (AOR =2.825, 95% CI: 1.166-6.843), education of spouse (AOR 0.361, 95% CI : 0.130–1.000), occupation of spouse (AOR = 0.261, 95% CI: 0.093 –0.739), monthly income of family > 20,000Nrs (AOR = 2.190, 95% CI: 1.041–4.606), planned pregnancy (AOR = 2.417, 95% CI: 1.047 –5.609), death of child (AOR = 3.153, 95% CI: 1.112 –8.944). Conclusions: This study demonstrated low antenatal care service utilization. Hence, there is a need to increase the availability and accessibility of antenatal care to all women. Keywords: Antenatal care (ANC); appropriate time of visit; child birth; pregnancy; reproductive age.